Heart flux in surface snow at Mizuho Station, Antarctica: Monthly values and errors - Kikuchi, Tokio (1983)
P(論文) Investigations are made on the determination of conductive snow heat flux at an Antarctic snow field, Mizuho Station, from the end of February to December 1979 during the first year of POLEX-South. Some preliminary analyses on the heat flux meter outputs raised questions on the data. As an alternative method, numerical differentiation and integration method is used to calculate snow heat flux from snow temperature. Errors accompanying the calculation are investigated, and it revealed that this method gives monthly heat flux with a relative error of about 10%. Snow temperature gradient in the surface layer is consistent with the present estimates. Estimated snow heat flux is compared with the results obtained at other sites in Antarctica. departmental bulletin paper